EUROPEAN RESPIRATORY SOCIETY PRACTICE GUIDELINES IN TREATMENT OF SARCOIDOSIS: CLINICAL APPROACH AND SUGGESTIONS - Marić, Nikola; Belić, Slobodan; Nikolić, Nikola; Stjepanović, Mihailo (Srpski medicinski časopis Lekarske komore, 2023)
Sarcoidosis can affect any organ and thus lead to a significant impairment of quality of life, even to an increase in mortality rate. Neurosarcoidosis, cardiac sarcoidosis, and pulmonary fibrosis in sarcoidosis are the forms of sarcoidosis with the highest mortality rate, and with the lowest response rate to current therapy. A group of experts in the field of sarcoidosis, supported by the European Respiratory Society, created practice guidelines on treatment of the most common forms of sarcoidosis, and provided suggestions for further research in order to create new therapeutic protocols. The evidence was obtained by reviewing literature. The aim of this paper is to bring these guidelines closer to doctors in daily clinical practice, in order to improve patients’ quality of life and reduce mortality from sarcoidosis.
Keywords: sarcoidosis; treatment; European respiratory society; corticosteroids; immunomodulators